Clinical impact of laparoscopic surgery and adhesion prevention material for prevention of small bowel obstruction. Issue 5 (18th March 2022) - Yamada, Takeshi; Hirata, Keiji; Ichikawa, Daisuke; Ikeda, Masataka; Fujita, Fumihiko; Eto, Ken; Yukawa, Norio; Kojima, Yutaka; Matsuda, Akihisa; Shimoyama, Rai; Ochiai, Hideto; Kumamoto, Kensuke; et al.
Abstract: Aim: Adhesive small bowel obstructions (SBO) are one of the most common complications following abdominal surgery, and they decrease patient quality of life. Since 2000, laparoscopic surgery has been employed with increasing frequency, as has adhesion prevention material (APM). In this study we tried to evaluate whether laparoscopic surgery and APM reduce the incidence of SBO. Methods: In Cohort 1, we included patients who developed SBO and received inpatient treatment between 2015 and 2018. We evaluated the elapsed time between precedent surgery and the onset of SBO, and what kind of surgery most often causes SBO. In Cohort 2, we included patients who underwent digestive surgery between 2012 and 2014 and evaluated SBO incidence within 5 y after the precedent surgery. Results: In all, 2058 patients were included in Cohort 1. Of these, 164 had experienced no precedent surgery. Among patients with a history of abdominal surgery, 29.7% experienced SBO within 1 y after the precedent surgery and 48.1% within 3 y. Altogether, 18798 patients were analyzed in Cohort 2. The incidence of SBO after laparoscopic colorectal surgery was lower than that of open colorectal surgery ( P < .001), and laparoscopic gastroduodenal surgery was also lower ( P = .02). However, there were no differences between laparoscopic and open surgery for other types of surgery. The use of APM had no effect on SBO incidence in any type of abdominal surgery. Conclusions: Laparoscopic surgery helps to reduce SBO incidence only in colorectal surgery, and possibly in gastroduodenal surgery. APM does not reduce SBO after abdominal surgery. Abstract : The incidence of small bowel obstruction after laparoscopic colorectal surgery was lower than that of open colorectal surgery ( P < .001), and laparoscopic gastroduodenal surgery was also lower ( P = .02). However, there were no differences between laparoscopic and open surgery for other types of surgery. The use of adhesion prevention material had no effect on the incidence of small bowel obstruction in any type of abdominal surgery.